Digital pain drawings are a useful and reliable tool for assessing patients with temporomandibular disorders. (16th April 2021) - Pitance, Laurent; De Longhi, Benjamin; Gerard, Eve; Cayrol, Timothee; Roussel, Nathalie; Cescon, Corrado; Falla, Deborah; Barbero, Marco
Abstract: Background: Temporomandibular disorders (TMD) are characterised by complex symptomatology and their assessment can be enhanced using pain drawings (PD). Objectives: To evaluate the location and extent of pain in people TMD using digital PD, and to explore their association with clinical features. Reliability of pain extent and pain location using PD was also assessed. Methods: Forty volunteers with TMD completed two consecutive digital PDs. Clinical features were captured from self‐reported questionnaire. Additionally, secondary hyperalgesia was measured using the pressure pain threshold (PPT). The correlation between pain extent and clinical features was investigated using Spearman rank correlation coefficients. Reliability of pain extent was evaluated using intraclass correlation coefficient (ICC) and Bland‐Altman plots. The Jaccard index was computed to assess the reliability of pain location. Results: Analysis of the PDs indicated that people with TMD commonly experience pain in other body regions including the neck, the shoulder and the low back. Except for PPT and pain catastrophising, all other clinical features were significantly correlated with pain extent. The ICCs of pain extent for all body charts were very high (ICCs 95% CI from 0.73 to 0.96), and Bland‐Altman plots showed mean biases close to zero with narrow limits of agreement. The reliability of pain location was also supported by Jaccard index mean scores above 0.68. Conclusions: People with TMD showed widespread pain, and pain extent was associated with pain intensity, neck and headache‐related disability, depression, anxiety, hyperventilation and central sensitivity. The reliability of measuring pain extent and pain location was confirmed.